Obesity and Mechanisms of its Negative Impact on the Cardiovascular System - S. V. Miklishanskaya; L. V. Solomasova; M. A. Mazur (Столичная издательская компания, 2020)
Currently, the number of obese people in the world is constantly increasing. Obesity has a direct negative impact on the heart and blood vessels, which can be considered not only as an appropriate response to an increase in the volume of circulating blood due to an increase in body weight, but also as a side tissue reaction of the myocardium to hormonal and metabolic changes inherent in obesity. Our review is devoted to the description of the mechanisms of influence of obesity on the structural and functional parameters of the heart, which create prerequisites for the development of cardiovascular diseases, as well as the existing contradictions. Currently, the accumulated data suggest that an excessive amount of adipose tissue, in addition to metabolic disorders, including insulin resistance, imbalance of adipokines and inflammation markers, leading to the development of lipotoxicity, can directly penetrate the myocardium and cause violations of its contractile properties, as well as affect the conduction of excitation pulses and provoke the development of rhythm and conduction disorders. The development of endothelial dysfunction in obesity ultimately leads to the development of atherosclerosis and coronary heart disease. In addition, obesity contributes to the emergence of risk factors for hypertension, diabetes, atrial fibrillation, chronic heart failure, obstructive sleep apnea syndrome. Given the differences in the literature on the effect of obesity on long-term outcomes in patients with cardiovascular diseases, it is important to conduct prospective studies on the role of individual factors and their combinations that affect the mortality of patients with cardiovascular diseases.